Multislice CT virtual endoscopy in pre-aortic stent grafting: optimization of scanning protocols. - Sun, Zhonghua; Chaichana, T.; Jiang, W.; Liu, B. (ISBME, 2008)
The purpose of this study was to investigate the optimal scanning protocols of multislice CT (MSCT) angiography in pre-aortic stent grafting, visualized on virtual endoscopy (VE). A series of scans were performed on a human aorta phantom with a 16-slice multislice CT scanner with the scanning protocols as follows: section thickness of1.0/1.5/2.0/3.0 mm, pitch value of 1.0/1.25/1.5, and reconstruction interval of 50% overlap. Signal to noise ratio and standard deviation (SD) of the signal intensity on VE images were measured to determine the image quality in relation to MSCT scanning protocols. Subjective assessment was performed by two observers evaluating the degree ofartefacts and the configuration of the renal ostium visualized on VE images. Our results showed that the scanning protocol with a section thickness of 2.0 mm resulted in the highest SNR and lowest SD compared to other protocols (p<0.05).Subjective assessment demonstrated that VE image quality was determined by section thickness, but independent of pitch values. We recommended the scanning protocol of section thickness 2.0 mm, pitch 1.5 with a reconstruction interval of 1.0 mm as the optimal one since it allows optimal visualization of VE images of aortic ostia, fewer artefacts and less radiation dose.